2015
DOI: 10.1002/gcc.22293
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations detected by conventional karyotyping using novel mitogens in chronic lymphocytic leukemia: Clinical and biologic correlations

Abstract: To clarify whether karyotype aberrations (KA) involving regions not covered by the standard fluorescence in situ hybridization (FISH) panel have independent prognostic relevance, we evaluated KA by conventional cytogenetics in a learning cohort (LC; n = 166) and a validation cohort (VC; n = 250) of untreated chronic lymphocytic leukemia (CLL) patients. In the VC, novel mitogens were used to improve metaphase generation and TP53, NOTCH1, and SF3B1 mutations were assessed. KA undetected by FISH were found in 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 33 publications
(62 reference statements)
4
49
1
Order By: Relevance
“…8 All patients were diagnosed and treated according to National Cancer Institute criteria. 9 The study was approved by the local ethics committee.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 All patients were diagnosed and treated according to National Cancer Institute criteria. 9 The study was approved by the local ethics committee.…”
mentioning
confidence: 99%
“…13 Furthermore, with the use of effective mitogens, cytogenetic abnormalities and, in particular, CK recently emerged as one of the novel biomarkers associated with an inferior outcome [4][5][6][7][8]12,20 and with the development of chemorefractoriness. 21 In conclusion, we showed for the first time that comorbidities and CK were associated with a worse outcome independently of CLL-IPI.…”
mentioning
confidence: 99%
“…The presence of chromosome aberrations was predictive of an inferior outcome in those patients without detectable aberrations by fluorescence in situ hybridization (FISH) 93. Unbalanced chromosome translocations, frequently occurring in the context of complex karyotype, were shown to be independent prognostic factors in a study94 and complex karyotype predicted for a shorter TTFT71 and OS95 by multivariable analysis. The prognostic value of complex karyotype was also demonstrated in relapsed/refractory CLL patients treated with ibrutinib-based regimens, where this parameter showed a stronger impact on the outcome than del(17p) 96.…”
Section: Resultsmentioning
confidence: 99%
“…Telomere length proved a reproducible predictor of the outcome but the detection method is not standardized yet, even if a recent study confirmed the reproducibility of results obtained with monochrome multiplex Q-PCR (MMQ-PCR) and single telomere length analysis (STELA), opening the way for the assay standardisation 56. Complex karyotype as detected by stimulation with novel mitogens66 may represent a novel predictor of unfavourable outcome 71,9597. While simple measures of disease burden such as stage and lymphocytosis do not play a role anymore as prognostic markers, host characteristics such as poor PS and advanced age still play a relevant role in predicting OS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the complex karyotype emerged as an independent predictor of inferior time to first treatment (TTFT) and shorter overall survival (OS) in patients investigated at diagnosis [29] or at disease progression [30] and in relapsed/refractory CLL treated with ibrutinib [31]. …”
Section: Introductionmentioning
confidence: 99%